Collaborations between National Olympic Committees and public authorities - Meier, H. E.; Garcia, B. (University of Münster, Loughborough University, 2019)
Executive summary ES 1. Sports autonomy represents, in essence, a first world concept, which emerged under very specific cultural and political conditions, which cannot be taken for granted. ES 2. Sports autonomy has been heavily refined due to the commercialisation of sport, regulatory failures and the regulatory efforts of public authorities. ES 3. The refinement of sports autonomy by the IOC, which calls for collaborative and coordinated efforts of NOCs and public authorities, represents a more realistic approach able to take the diversity of the Olympic movement into account. ES 4. The NOCs are involved in complex and multi-faceted relationships; they depend on different government resources to achieve their goals. Accordingly, they have to enter collaborations. ES 5. Understanding the role of NOCs in national sport policy making requires a more detailed look at the specific collaborations the NOCs have entered. ES 6. The detailed case studies on four NOCs illustrate the substantial diversity within the Olympic movement. The Western model of a sport system based on strong volunteer movement is rather exceptional and should therefore not be made into a key pillar for a global theory of sport governance. ES 7. The NOCs are integral part and key stakeholders within the national sport systems. This role makes tensions between NOCs and public authorities and/or between the NOCs and other sport organisations very likely. ES 8. The overall structure of the national sport system determines key parameters in which the NOC can move. A potential merger of the NOCs with the national sports commission/ council will make it even more difficult for the NOCs to dissociate themselves from the public structures of sport in the country. In any case, the NOCs have to decide between being part of the public sport system or remain less embedded, but with limited activities. ES 9. In combination with the general structure of national sport systems, formal regulatory and legislative structures are decisive for the NOCs to develop their activities. Constitutional and legal frameworks might be more or less permissive and restrictive for the NOCs as well as national policy makers. ES 10. Clear frameworks for collaborations between the NOCs and public authorities. The most efficient collaborations are those in which the distribution of responsibility and deliverables are transparent for both partners. ES 11. The NOCs should dedicate their political efforts to negotiating reliable and clear memorandums of understanding. The IOC`s insistence on some minimum sports autonomy provides the NOCs with substantial bargaining leverage. ES 12. Funding plays a key role for the NOCs. Almost all NOCs are heavily reliant on government or public money. This reliance takes different forms and has different effects. If NOCs are not willing to restrict their activities, they have to be able to negotiate the terms of public funding and to be able to adapt to the specific way by which government funding is provided. ES 13. IOC funding is essential and strategically relevant for NOCs in developing countries. ES 14. All NOCs investigated are very professional and proactive organisations pursuing strategic visions. The NOCs in developing countries have clearly benefitted from IOC funding and IOC sport management or administration programmes. Management and administrative skills are important for the NOCs to navigate in national sport policy making. ES 15. Personal and political relations are very important for the role of the NOCs within national sport policy making. These relations can mediate the impact of harder parameters, such as, the structure of the national sport system, the regulatory framework and the conditions for public funding. The NOC leadership needs to create high-level political ties, which can have ambiguous effects.